A novel nutritional score based on serum triglyceride and protein levels predicts outcomes of intrahepatic cholangiocarcinoma after curative hepatectomy: A multi-center study of 631 patients - Cai, Yunshi; Xue, Shuai; Li, Jiaxin; Xiao, Heng; Lan, Tian; Wu, Hong (Frontiers in Nutrition, 2022)
Abstract Background: High serum triglyceride (STG) level is a well-established pathogenic factor for cardiovascular diseases and is associated with the risk of various malignancies. Nevertheless, the role of STG level in intrahepatic cholangiocarcinoma (ICC) remains uncertain. Methods: A total of 631 ICC patients treated with curative hepatectomy in two centers (517 in the discovery set and 114 in the validation set) were retrospectively analyzed. Kaplan-Meier survival analysis was used to assess the outcomes of the patients with different STG levels. Time-dependent receiver operating characteristic (ROC) analysis was conducted to compare the prognostic value of STG with other established indexes. The Triglyceride-Albumin-Globulin (TAG) grade was introduced and evaluated using the time-dependent area under curves (AUC) analysis and decision curve analysis (DCA). Results: Patients with increased STG levels and decreased albumin-globulin score (AGS) were correlated with improved overall survival (OS) and recurrence-free survival (RFS). STG level≥1 mmol/L was an independent protective factor for surgically treated ICC patients. The predictive value of the TAG grade was superior to the STG or the AGS alone. In decision curve analysis, the net benefits of the TAG grade in the discovery and validation set were higher than STG and AGS. Conclusions: The current study presented strong evidence that ICC patients with higher preoperative STG levels had preferred long-term surgical outcomes. The novel nutritional score based on serum triglyceride, albumin and globulin levels was inextricably linked to the prognosis of the surgically treated ICC patients. Evaluation of the TAG grade before curative hepatectomy may be beneficial for risk stratification and clinical decision support.